Formação e atuação do professor de química : um estudo sobre a transposição didática dos modelos atômicos - Santana, Rafael de Jesus (2010)
This Study aimed to investigate how was the didactic transposition of atomic models in the first degree course in Chemistry, Sergipe in Federal University and two schools in the Network State Public High School in Aracaju-SE. Throughout the study, we expose a discussion among theorists with regard to the formation and action of teachers, didactic transposition and atomic models, aiming to show the different perceptions on this theme which has been researched and discussed by many researchers. Used as theoretical support for the discussion of the didactic transposition, the contributions of Chevallard (1991), which defines it as the work that makes an object of knowledge to teach, a teaching object. We chose to investigate one of the basic concepts of chemistry, the first models that explain the constitution of matter, because the chemistry, as science seeks to explain nature using models (theoretical representations). This research approach was qualitative and quantitative analysis, drawing on the comparative method, using pre-defined categories by content analysis (BARDIN, 2010). The tools utilized for data collection, semi-structured interviews and tests, respectively applied to teachers and students. Thus, the study sample was defined by four former students of the UFS and teachers from two schools in the State Schools of Aracaju-SE, being a center of excellence (in which students study in two shifts) and in other school that students study just one part, and forty students, twenty in each school studied, chosen randomly. We tried to analyze the didactic transposition of atomic models at two levels: the teacher who learns to be a teacher in the initial training course at the Sergipe in Federal University and high school educators that makes the didactic transposition of atomic models for students. Moreover, we noted and correlate the knowledge learned by students on the atomic models with the knowledge that teachers said they taught. The data collected and organized into categories that were indicative of the didactic transposition of atomic models was performed inadequately.